Quarenteners: leituras partilhadas durante a pandemia da Covid-19 - Rosa, Ana Paula Gomes (2022)
In March 2020, the World Health Organization declared that the world was facing a pandemic caused by the new coronavirus, SARS-CoV2. This event had profound impacts on all dimensions of collective life and was no different in the field of reading, which came to be valued as a means of providing relief, assistance and reflections so that readers could understand the moment they were experiencing. There were several stimuli for reading, observed on the websites of publishers, newspapers, professional associations, universities and virtual communities, especially booktubers, accompanied by the growth in the search for virtual reading groups and books. Based on this finding, the objective of this dissertation is to follow the increase in shared readings amid the Covid-19 pandemic in interactive internet media, in order to understand reading practices in this context. The data were obtained through a survey of online newspapers, lives and videos broadcast by YouTube which, after being systematized, were analyzed. We focus the study on channels that direct and indicate readings, proposing times of shared reading in virtual spaces and in real time, as well as conversations about the importance of reading and books, especially in the current context. We argue that virtual readers have come to value and re-signify literary reading, have formed interpretive communities by the perception that they share the same reading interests and, therefore, are linked to the same group of belonging.